Proceedings of International Symposium on Radiation Detectors and Their Uses (ISRD2016) 2016
DOI: 10.7566/jpscp.11.010001
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Increase of the Radiation Chemical Yield for Loss of Carbonate Ester in PADC Detector where the Track Overlapping of 28 MeV Electrons Becomes Significant

Abstract: The latent track structure of 28 MeV electrons in poly(allyl diglycol carbonate), PADC, has been investigated using FT-IR spectral method. The density of ether decreases linearly with increasing the fluence. Chemical damage parameters of effective track radius, damage density and radiation chemical yield, for loss of ether are evaluated as 0.023 nm, 0.01 scissions/nm and 19 scissions/100 eV, respectively. The derived values are compared to that of previous ones from gamma ray, protons and heavy ions exposures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 14 publications
(28 reference statements)
2
10
0
Order By: Relevance
“…In the later, this was modified as that the value was valid above the critical dose of about 60 kGy [ 26 ]. Through the FT-IR studies on the effects of 28 MeV electron beams on PADC, applying the track overlapping model [ 42 , 50 , 51 , 52 ], it was found that the carbonate ester was radiation-sensitive after the damage of the ether in the same repeat-unit [ 25 ]. Below the critical dose, carbonate ester was hardly damaged by low- LET radiations, including 1.5 keV ultra-soft X rays [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the later, this was modified as that the value was valid above the critical dose of about 60 kGy [ 26 ]. Through the FT-IR studies on the effects of 28 MeV electron beams on PADC, applying the track overlapping model [ 42 , 50 , 51 , 52 ], it was found that the carbonate ester was radiation-sensitive after the damage of the ether in the same repeat-unit [ 25 ]. Below the critical dose, carbonate ester was hardly damaged by low- LET radiations, including 1.5 keV ultra-soft X rays [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Following on these experiments we developed a thinning process of PADC films to reduce the thickness to less than 3 µm, with a precise and accurate estimation of their thickness [ 15 ]. Thanks to this new material, off-line measurements of protons and heavy ions (He, C, Ne, Ar, Fe, Kr and Xe) were made, covering the stopping powers ranging from 1.2 to 12,000 eV/nm [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], as well as low- LET radiations [ 20 , 21 , 24 , 25 , 26 ]. As a reference, effects on exposure to ultraviolet (UV) photons with a wavelength of 222 nm were also executed [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following on these experiments we developed a thinning process of PADC films to reduce the thickness to less than 3 µm, with a precise and accurate estimation of their thickness [16]. Thanks to this new material, off-line measurements of protons and heavy ions (He, C, Ne, Ar, Fe, Kr and Xe) were made, covering the stopping powers ranging from 1.2 to 12,000 eV/nm [15][16][17][18][19][20][21][22][23], as well as low-LET radiations [20,21,[24][25][26]. As a reference, effects on exposure to ultraviolet (UV) photons with a wavelength of 222 nm were also executed [27].…”
Section: One Decade Of Methodological and Conceptual Evolutionmentioning
confidence: 99%
“…And in the central region, parts of polyethylene-like structure are also modified. Through the experiments using low-LET radiations of 28 MeV electron beams [25], gamma rays from 60 Co and 1.5 keV ultra-soft X ray [26], it was found that a single electron can cleave ether but it cannot break the carbonate ester. Carbonate ester turns out to be radiation-sensitive when the adjacent ether is lost.…”
Section: One Decade Of Methodological and Conceptual Evolutionmentioning
confidence: 99%